"After all, we own our bodies." Towards women's bodily autonomy: Liberalizing abortion laws in Iceland and Ireland - Heiða Ragney Viðarsdóttir 1995- (2023)
Abortions are a disputed topic worldwide and are highly politicized. Abortion laws have largely been liberalized on a global scale but have also faced a global onslaught that threatens women’s rights to be reversible. This thesis is part of a larger research project that explores a global backlash against abortion rights, but instead of looking at how the backlash presents itself, this thesis explores how Iceland and Ireland liberalized their abortion laws amidst a global backlash. This study explores what kind of discourse can be observed when liberal abortion laws were passed in the two countries. The research uses critical discourse analysis to explore the data, which was composed of online newspaper articles in Ireland and parliamentary debates plus online newspaper articles in Iceland. The main findings showed that discourse in the two countries showed some similarities, such as that women’s bodily autonomy was an important reason for liberalizing abortion laws as well as that women should be trusted to make decisions for themselves and their futures. Differences in the discourse could also be observed; while Ireland focused on making abortion safe and legal within Ireland, Iceland focused on women’s bodily autonomy. Þungunarrof er umdeilt umræðuefni um heim allan og er hápólitískt. Lög um þungunarrof eru almennt að verða frjálslyndari á heimsvísu en það hefur orðið bakslag víða sem ógnar því að réttindi kvenna geti verið afturkræf. Þessi ritgerð er hluti af stærri rannsókn sem kannar alþjóðlegt bakslag gegn þungunarrofsréttindum en þetta verkefni skoðar hvernig Ísland og Írland komu frjálslyndari þungunarrofslöggjöf á fót á meðal alþjóðlegs bakslags. Í þessari rannsókn var orðræðugreint umræður þegar frjálslynd þungunarrofslöggjöf voru sett í löndunum tveim. Í rannsókninni er stuðst við gagnrýna orðræðugreiningu til þess að greina gögn sem safnað var fyrir rannsóknina. Gagnasöfnun fyrir Írland var samsett úr blaðagreinum af netinu en á Íslandi var notað blaðagreinar af netinu og einnig þingumræður. ...